Ratio of roughage to concentrate for fattening heifers - Richardson, D.; Baker, F.H.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Fifty Hereford heifers were divided into five lots as equally as possible on the basis of weight, size, conformation, and previous treatment. The heifers were wintered, 10 per loot, as calves on the following rations: (1) alfalfa hay and 3 pounds of corn; (2) Atlas sorghum silage, 2 pounds milo grain, and 1 pound cottonseed meal; (3) Atlas sorghum silage and 3 pounds special supplement; (4) prairie hay, 2.6 pounds milo grain, and 1 pound cottonseed meal; (5) corn cobs, 2.25 pounds milo grain, and 1. 5 pounds cottonseed meal. Two heifers from each lot on the above wintering rations were allotted to each of the five lots in this experiment. That gave a total of 10 animals per lot. The feeds used were good quality, chopped alfalfa hay, coarsely cracked milo grain, and corn. One lot of animals received corn so that a comparison of milo grain and corn could be made. Water, salt, and ground limestone were provided free choice at all times.
Keywords: Beef; Roughage; Gain; Digestibility